ESL undergraduates’ knowledge and patterns of plagiarism in academic writing, and university academic integrity policies in Malaysia - Zangenehmadar, Samaneh (2014)
The increasing prevalence of plagiarism has recently become a serious issue in academia. To prevent plagiarism, it is necessary to understand students‘ knowledge about plagiarism, what they perceive to be the factors contributing to plagiarism, their knowledge of the conventions of writing, and university policies on academic integrity. This study was undertaken with four objectives in mind: (1) to investigate the extent of the awareness of plagiarism among Malaysian undergraduates; (2) to identify patterns of plagiarism in students‘ academic writing; (3) to compare the level of students‘ plagiarism based on the Internet and printed sources of information; and (4) to examine the integrity policies of top five Malaysian universities. This descriptive study used a mixed-method design to analyze both qualitative and quantitative data. To investigate students‘ knowledge of plagiarism, pre-determined questionnaires were randomly distributed among 400 undergraduates at a local public university. Moreover, to identify the existing plagiarism patterns and examine the level of plagiarism in students‘ writing, essays were randomly collected from 70 students of the 400 surveyed participants. Half of the 70 students (n=35) were randomly given two printed articles on global warming to read, and based on their reading, they constructed an essay of about 500 words by typing it using MS Word. The remaining half of the students (n=35) were emailed the Internet URL links of the two sources (of the same articles) and given instructions to write the 500-word essays on the same topic. The essays (two sets of 35 essays) were checked using Turnitin, a text-matching software. The originality reports of students' essays produced by Turnitin were then checked against the original sources to code various instances of plagiarism. In addition, to investigate the integrity policies of top five universities in Malaysia, the documents were sourced from the websites of the relevant universities and coded based on core elements of an exemplary academic integrity policy.The results of the study indicated that the majority of the students are more aware about definitions rather than forms of plagiarism. They mentioned the ease of copying and pasting from the Internet as the most common contributing factor to plagiarism. The findings of the study also showed that the higher the students‘ language proficiency is, the higher is their level of knowledge of plagiarism. In addition, students from the field of social science have more knowledge about plagiarism than those from the Pure Sciences. Direct copying with no reference and quotation marks is the most frequent plagiarism pattern in students‘ writing. Plagiarism patterns in essays based on the Internet and printed sources are found to be significantly different. Similarity indices of academic essays using Internet sources are also significantly higher than those of printed sources. Finally, the results from the investigation of Malaysian university integrity policies indicated that policies of university A, B, and D are easy to locate and access. Universities A, B, and C apply both punitive and educative approaches to address plagiarism. They also provide a clear outline of the responsibility for academic integrity which must be borne by the students and the staff of the university. The study recommends that lecturers need to incorporate specific instructions about citation practices and referencing skills in ESL writing courses to reduce the occurrence of plagiarism among students. The study provides universities with new insights to highlight the exemplar of five core elements in Malaysian university policies.